Penguatan Partisipasi Warga Banua Melalui Prinsip Ecological Citizenship Pada Program Kampung Iklim Untuk Mewujudkan Ketahanan Lingkungan Lahan Basah Berkelanjutan - Suroto, Suroto; Ari Nugroho, Dedy; Amelia Rafiah, Rika (Universitas Nusantara PGRI Kediri, 2021)
This research article contains a study of research results that focus on government efforts and community participation in seeking environmental resilience for each generation, through their involvement in the climate village program in Banjarmasin City. The city of Banjarmasin has natural characteristics which are dominated by river areas. Community participation and government programs in environmental aspects need to be carried out to ensure the existence of rivers so that they always bring benefits to the community. This research article was compiled using a phenomenological qualitative research approach. Researchers explain research findings data in a series of words that can describe data based on facts. The type of qualitative research used in this study is a phenomenological descriptive research type. The results obtained from the research carried out are: (1) Banjarmasin City Government Strategy in an effort to strengthen Ecological Citizenship in the Climate Village Program, (2) The form of participation shown by the community in efforts to strengthen Ecological Citizenship in the Climate Village Program, (3) City Government barriers Banjarmasin and the people of Banjarmasin City in an effort to strengthen Ecological Citizenship in the Climate Village Program. The results that will be obtained in this study are expected to be able to produce shared knowledge about the importance of community participation in an effort to build commitment to contribute to wetlands. Strengthening community participation is a very important thing to strive for together, because with a participatory community, there will be many things that can be optimized for the common interest, including how to manage wetlands. Community participation must be increased with the synergy of all parties, both the government and the community.